Evolution of bacteriophage phi C174. V. Alignment of the phi X174, G4, and St-1 restriction enzyme cleavage maps. - Grindley, J N (1978)
The restriciton enzyme cleavage maps of bacteriophage phiS174, G4, and St-1 were aligned by two-dimensional filter hybridization. These studies show that the basic genome structure of phiX174 is conserved in the other two bacteriophage. However, the data also suggest the existence of regions of nonhomology.